Efek Biologi dari Mikoriza Vesikular Arbuskular untuk Meningkatkan Pertumbuhan Tanaman dan Stabilitas Agregat Tanah - Hanggari Sittadewi (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2021)
Vesicular-arbuscular mychorrizae (MVA) is a key player in triggering vegetation development and soil reinforcement due to its potential to increase plant growth and soil aggregate stability. In terms of enhancing plant growth, the vesicular-arbuscular mycorrhizae provides greater and more efficient access through the fungal hyphae for nutrient absorption and delivery to the plant. From the side of soil mechanical, the potential of vesicular-arbuscular mycorrhizae is to increase the soil aggregate stability. These potentials, in their application can contribute to soil and slope stability. The characteristics and biological effects of vascular-arbuscular mycorrhizae to increase plant growth and soil aggregate stability in the correlation to slope stability will be discussed in this paper.